2013
DOI: 10.1212/wnl.0b013e318293e14e
|View full text |Cite
|
Sign up to set email alerts
|

Child Neurology: Diagnosis of Lambert-Eaton myasthenic syndrome in children

Abstract: Objective: To report a case of Lambert-Eaton myasthenic syndrome (LEMS) in a child and review the existing literature of LEMS in children. Methods:We report a pediatric case of LEMS with the classic clinical triad of proximal weakness, autonomic dysfunction, and areflexia; the characteristic increment in compound motor action potential on high-frequency repetitive nerve stimulation; and positive serum P/Q-type voltagegated calcium channel antibodies. Only 11 pediatric cases of LEMS have been reported in the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…Regarding other types of myasthenia, we found no patients in the population-based cohort with Lambert-Eaton syndrome and very few patients with confirmed antibody positive Lambert-Eaton myasthenia overall (2 cases over a 50-year period), similar to a recent report. 19 We did not report a single case of neonatal autoimmune myasthenia, similar to a study in the UK that found neonatal myasthenia to be extremely rare (3 children per year). 11 There are a number of limitations to the findings of this study.…”
Section: Discussionsupporting
confidence: 75%
“…Regarding other types of myasthenia, we found no patients in the population-based cohort with Lambert-Eaton syndrome and very few patients with confirmed antibody positive Lambert-Eaton myasthenia overall (2 cases over a 50-year period), similar to a recent report. 19 We did not report a single case of neonatal autoimmune myasthenia, similar to a study in the UK that found neonatal myasthenia to be extremely rare (3 children per year). 11 There are a number of limitations to the findings of this study.…”
Section: Discussionsupporting
confidence: 75%
“…Recently, sympathicomimetics (SM) have been introduced successfully as clinical treatment of neuromuscular transmission disorders called congenital myasthenic syndromes (CMSs) (3,4). Fittingly, muscle weakness is a hallmark of several autonomous nervous system disorders, including chronic fatigue syndrome (5), congenital insensitivity to pain (6), adrenal insufficiency (7,8), complex regional pain syndromes (9,10), and Lambert-Eaton myasthenic syndrome (11)(12)(13). Because, furthermore, beta-blockers lead to increased susceptibility to muscle fatigue (14) and modulate neuromuscular activity of drugs applied during anesthesia (15), we became interested in addressing sympathetic innervation of skeletal muscle.…”
mentioning
confidence: 99%
“…There are case reports of infants with CMS (including choline acetyltransferase deficiency caused by CHAT mutations) who have subsequently been found to have abnormalities on fast or prolonged RNS . Although these diagnoses are individually rare, all have potential clinical implications if overlooked, including apnea (botulism or CHAT mutations) or paraneoplastic causes (LEMS) …”
Section: Resultsmentioning
confidence: 99%